KODE ETIK GURU SEBAGAI LANDASAN MORAL DALAM MENGHADAPI TANTANGAN PENDIDIKAN DI ERA DIGITAL - Amilatusholekha, Mufida; Aulia, Nazwa Intan; Marfu'ah, Jihan Aulia; Nashrulloh, Muhammad Iqbal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation is not only revolutionizing learning modalities but also fundamentally reshaping the ethical dimensions of the teaching profession. This study aims to investigate the crucial role of the teacher code of ethics as the primary moral foundation in mitigating various contemporary educational challenges in the dynamic digital era. Using a qualitative method with a literature review approach, an in-depth analysis was conducted on various recent scientific literature published in the last decade. The findings of this study confirm that the code of ethics, as an articulation of professional moral norms and principles, functions critically as a regulatory compass for educators. Amid massive technological disruption that often triggers dilemmas regarding character education, disparities in technological competence among teachers, and the lack of comprehensive ethical regulations, the code of ethics remains a vital instrument. Essential internal values such as personal integrity, protection of student data privacy, academic honesty, and professionalism in social media use must be established as the primary foundation. This is crucial to ensure that technological advancements do not erode the dignity, honor, and noble authenticity of the teaching profession. Today’s educators are required to balance digital proficiency with a strong moral commitment to uphold the moral quality of the nation’s future generations.